INVESTIGATION OF THE ROLE OF LIME UNDER SLAGGING AND INERT-GAS SECONDARY STEEL REFINING - Denis Anatolyevich Bakhayev; Alexander Ivanovich Kochetov; Alexander Yuryevich Kem; Alexey Alexandrovich Ansimov (Advanced Engineering Research, 2013)
It is shown that the creation of such technologies is caused by the necessity of making standard high-quality steel in composition and temperature. The secondary steel refining provides these conditions and, consequently, the efficient operation of the steel continuous casting plants. The commercially proven experimental results on the lime consumption effect on the slagging processes in the electric arc furnaces and on the further secondary refining in the ‘ladle-furnace’ units are presented. A flow chart of the complex processing “Electric Arc Furnace → Secondary Refining → Steel Continuous Casting Plant” is offered. It eliminates the increase of the slag oxidation degree under bottom blowing, aluminum loss in the bucket, and the increase of the oxygen concentration in the liquid steel. The proposed technology solutions to optimize the lime flow, slag adjustment, and to regulate the steel ladle stirring regime have permitted to raise the basic technical and economic indicators of the steelmaking at Oskolsky electrometallurgical works.